2-Year assessment of tissue biostimulation with low-level laser on the outcomes of connective tissue graft in the treatment of single gingival recession: A randomized clinical trial - Santamaria, Mauro Pedrine [UNESP]; Fernandes-Dias, Stephanie Botti [UNESP]; Araújo, Cassia Fernandes [UNESP]; Da Silva Neves, Felipe Lucas [UNESP]; Mathias, Ingrid Fernandes [UNESP]; Andere, Naira Maria Rebelato Bechara [UNESP]; Jardini, Maria Aparecida Neves [UNESP] (Wiley, 2017)
Background: Periodontal wound healing has been accelerated by different low-level laser therapy (LLLT) protocols. However, just a few studies have evaluated use of this therapy adjunctive to periodontal plastic surgery procedures. The present study shows 2-year results of a connective tissue graft (CTG) associated with LLLT in the treatment of gingival recession (GR) defects. Methods: Forty patients presenting Miller Class I and II GRs were previously treated by CTG (control group; n = 20) or CTG + LLLT (test group; n = 20). A diode laser (aluminumgallium- arsenide, 660 nm) was applied to test sites immediately after surgery and every other day for 14 days (total of eight applications). After a follow-up of 2 years, clinical and esthetic evaluations were performed in 36 patients. Results: Mean percentage of root coverage was 93.43% for the test group and 92.32% for the control group (P = 0.55). Complete root coverage was 79% (n = 15) for the test group and 76% (n = 13) for the control group (n = 13) (P = 0.80). Both groups showed esthetics maintenance after 2 years. Conclusion: Within the limitations of this study, results indicate that LLLT showed no additional benefit in the long term when associated with a CTG in the treatment of Miller Class I and II GRs.
Keywords: Esthetics; Gingival recession; Low-level light therapy